Parent–child interaction therapy in the treatment of children who stutter: a single-subject longitudinal study - Belal, Manar; Amer, Ayman; Abou-Elsaad, Tamer (The Egyptian journal of otolaryngology, 2024)
Background The study aimed to investigate the efficacy of the indirect home-based program, including parent–child interaction therapy (PCIT), in reducing the severity and degree of stuttering in young children to be used as a treatment program for young children who stutter. Methods A longitudinal multiple single-subject study was conducted on 16 Arabic-speaking Egyptian children aged 4–7 years who stutter. All parents and children were evaluated during the first clinic visit to assess stuttering and to start the clinic-based therapy. After six weeks, a follow-up was done. After three months of the home-based therapy program, a re-assessment of the degree and severity of stuttering was done using the Bloodstein classification of stuttering severity and Stuttering Severity Instrument-3 (SSI3). Results Mean SSI3 pre-therapy was 17.5 and decreased to 11 post-therapy. Before therapy, most cases were moderate stuttering 68.8%, 25% were mild, and 6.3% were severe; after treatment, most cases became mild stuttering (75%), 12.5% became very mild, and 12.5% became moderate stuttering according to SSI3 scores, also mean Bloodstein pre-therapy was II and decreased to I post-therapy. Conclusion An indirect home-based program, including PCIT, efficiently reduces the severity and degree of stuttering in young children and justifies its use as a treatment program for children who stutter.